2020
DOI: 10.3892/or.2020.7886
|View full text |Cite
|
Sign up to set email alerts
|

KRT7 promotes epithelial‑mesenchymal transition in ovarian cancer via the TGF‑β/Smad2/3 signaling pathway

Abstract: Keratin 7 (KRT7) is a member of the keratin gene family. KRT7 is abnormally expressed in various types of cancer and promotes the malignant progression of tumors. However, the role of KRT7 in ovarian cancer remains unclear. The present study aimed to validate the role of KRT7 in ovarian cancer progression. KRT7 expression levels in patients with ovarian cancer were analyzed using data obtained from the Human Protein Atlas and The Cancer Genome Atlas databases. KRT7 mRNA and protein expression levels were upreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 40 publications
1
40
0
Order By: Relevance
“…The literature is scarce and mixed regarding KRT7 regulation in cancer. It was observed in a recent publication that KRT7 overexpression in ovarian cancer cell lines was associated with increased proliferation, migration and EMT marker expression through the regulation of the TGF-β/Smad2/3 [ 23 ]. These results obtained on HGSC cell lines differ from our findings which show that KRT7 expression is not correlated with EMT markers in HGSC tissues and emphasizes the need to more fully characterize KRT7 functions in HGSC progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature is scarce and mixed regarding KRT7 regulation in cancer. It was observed in a recent publication that KRT7 overexpression in ovarian cancer cell lines was associated with increased proliferation, migration and EMT marker expression through the regulation of the TGF-β/Smad2/3 [ 23 ]. These results obtained on HGSC cell lines differ from our findings which show that KRT7 expression is not correlated with EMT markers in HGSC tissues and emphasizes the need to more fully characterize KRT7 functions in HGSC progression.…”
Section: Discussionmentioning
confidence: 99%
“…KRT7, KRT18, KRT19 protein expression in tumors were reported to predict prognosis in several cancer types [ 18 , 19 , 20 , 21 , 22 ]. However, despite reported functions of KRTs in tumor progression, relatively little is known about their value as prognostic markers in the context of HGSC [ 17 , 23 , 24 , 25 ]. Interestingly, we previously showed that KRT7 and KRT19 mRNA were elevated in OC compared to borderline tumors [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…KRT5 is found in a population of basally located CD44 + stem-like cells in the FTE, for which its population is expanded in serous cancer samples [ 227 ]. KRT7 upregulates integrin β1-FAK signaling and matrix metalloproteinase expression, promoting cell matrix adhesion [ 241 ] and extracellular matrix degradation [ 228 ], respectively. The homeobox protein DLX-1 is a mediator in TGF-β1/SMAD4 signaling in ovarian cancer [ 224 ], which promotes EMT and cell stemness phenotypes [ 242 ].…”
Section: Foxm1 Oncogenic Functionsmentioning
confidence: 99%
“…Among the 6-lncRNA signature, studies have found that KRT7-AS can promote tumor cell proliferation and migration, and KRT7 may promote epithelial-to-mesenchymal transition (EMT) of OC through TGFβ/Smad2/3 signaling pathway [28][29][30]. In our study, USP30-AS1 was regarded as a tumor suppressor factor.…”
Section: Discussionmentioning
confidence: 67%